2012
DOI: 10.4314/ajid.v6i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in Malaria Control in Olorunda Local Government Area, Osun State, Southwestern Nigeria

Abstract: Malaria is a major health burden in developing countries and needs multiple strategies for its control. Community participation as one of the strategies for malaria control promotes self-awareness and confidence, causes the people to examine the problems and to think positively about the solutions. The study was aimed at assessing the level of community participation in malaria control in Olorunda local government area of Osogbo, Osun state, Nigeria. The study employed a cross-sectional descriptive design. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
2
8
1
Order By: Relevance
“…The results indicated that insecticide treated net may be related to having few compare to the number of beds that the household members were using or other misconceptions related to sleeping under insecticide treated net. The results also are quite different from that found by (Bamidele & Ntaji, 2012) where only 23% used bed nets to protect themselves. While the high level of use of mosquito nets is good, one should be mindful of non-sleeping times that they did not use mosquito nets.…”
Section: Discussioncontrasting
confidence: 95%
“…The results indicated that insecticide treated net may be related to having few compare to the number of beds that the household members were using or other misconceptions related to sleeping under insecticide treated net. The results also are quite different from that found by (Bamidele & Ntaji, 2012) where only 23% used bed nets to protect themselves. While the high level of use of mosquito nets is good, one should be mindful of non-sleeping times that they did not use mosquito nets.…”
Section: Discussioncontrasting
confidence: 95%
“…Hence SPR appears to be higher in study area as compared to the control area, the "at risk" population is clearly defined in the study area and therefore the sequential decrease in the SPR in the study area is an indirect indication of the effect of the interventions carried out in the study area (Table 3). 7,8 The decrease in MBER is evident in study area in the year 2010 as compared to the control area. The SPR reduction is more pronounced in the study area in 2010 as compared to the year 2009.The variations in SPR in control area becomes indeterminate, since the denominator includes both fever and non-fever cases ( Table 4).…”
Section: Discussionmentioning
confidence: 86%
“…Every member in the community gets to participate in the planning process and decision making and this ensures sense of ownership of the water resource. Bamidele et al (2012) agrees that community participation promotes self confidence and awareness and also causes people to examine their problems and to think positively about the solutions.…”
Section: Willingness To Participate In Rainwater Harvestingmentioning
confidence: 99%